A retrospective nationwide study of the dental caries experience of New Zealand children with orofacial cleft. Issue 1 (9th October 2019) - Fowler, Peter V.; Corbett, Abbey; Lee, Martin; Thompson, John M. D.
Abstract: Objectives: To investigate the dental caries experience of New Zealand children born with orofacial cleft (OFC), to compare this to age‐specific national population‐based data and to investigate any differences by demographic characteristics, cleft type and exposure to community water fluoridation. Methods: Nationwide retrospective study of 554 dental records from 478 children born after 1 January 2000 with OFC were assessed at aged 5 (n = 333) and 12 years (n = 221), with 76 children (15.9%) having records at both ages. Community Oral Health Service records were analysed to determine dental caries experience (dmft/DMFT). Logistic regression was used to assess the likelihood of having experienced dental caries (d 3 mft/D 3 MFT ≥ 1) and multivariable models for variables including demographic characteristics, cleft type and exposure to community water fluoridation. Results: A higher (49.6%) caries prevalence (dmft ≥ 1) and mean dmft at 5 years old (2.3; SD 3.6) were found in children with OFC than 5‐year‐olds in the general population (prevalence 40.4% and mean dmft 1.8). The 12‐year‐old (37.6%) caries prevalence (DMFT ≥ 1) and mean DMFT 0.8 (SD 1.4) were similar to population‐based data (caries prevalence 37.3% and mean DMFT 0.9). Children with caries (dmf/DMF ≥ 1) had means of 4.8 (SD 3.8) at age 5 and 2.1 (SD 1.4) at age 12 years. Greater caries experience was associated Pacific and Māori ethnicity, and not receiving community water fluoridation. No differences were detected by sex or cleft type. Conclusion: The dental caries experience for 5‐year‐old children with OFC was poor in relation to population‐based data and similar for 12‐year‐olds. Preventive guidelines for children with OFC from an early age should be a priority, along with the extension of community water fluoridation coverage.